Perbandingan Penggunaan Database OLTP dan Data Warehouse - Spits Warnars (Universitas Raharja, 2014)
As a permanent storage for business process transaction, database is a crucial and the needed for the system. Using database often does not match with the ability and functionality and even is it possible as theory said about using transaction database and beyond the advantages and disadvantages, separating using between transactional database and database for decision making will mine the ability and the powerful database as much as possible. Beside that daily transaction will increase the database capacity month by month and year by year and will decrease the performance, especially for customer daily services. Separating between database transaction and database for decision making will decrease connection to daily database transaction and increase daily database transaction as which is run by application and will implicate the increasing customer satisfaction. Moreover making the strategic reports for decision making never ever become a nightmare and unimportant thing. Differentiation efficiency for saving the amount of data byte and effectiveness the query speed in sql statement in order to make the decision making reports will be used as an approach for justification.